Depression in Patients with Diabetes Mellitus-an Analytical Study in Rajshahi - Hasan, Md Aminul; Hoque, Md Azizul; Hossain, AA Mamun; Sardar, Md Amzad Hossain; Amin, Md Ruhul; Sheherin, Sonia (TAJ: Journal of Teachers Association, 2021)
Background: Depression is one of the most common comorbid psychiatric disorders associated with diabetes mellitus (DM), and it impacts glycemic control. Optimal management of depression may lead to better control of glucose levels in DM. Objectives: The aim of this study was to assess depression in patients with DM and to compare it with healthy control and to determine the association of depression with glycemic control and socio-demographic profile in patients with DM and healthy control. Patients and methods: This cross-sectional comparative study was conducted among 140 patients with DM attending Rajshahi Medical College Hospital and Diabetic Association Hospital, Rajshahi, from July 2014 to June 2016. Subsequently, 140 age-matched healthy controls were included in this study. The DSM-V criteria were used to diagnose depression and the severity of depression was assessed by the Hamilton rating scale for depression. Blood glucose control was assessed by measuring HbA1c and categorized as: good glycemic control <7%, fair glycaemic control 7-8% and > 8% considered as poor glycemic control. Results: The proportion of depression was significantly higher in the patient (51, 36,4%) than in the control (20,14.3%) (X2= 18.256, df= 2, p <0.001). Among patients 13 (9.28%) had mild depression, 23 (16.42%) had moderate depression and 15 (10.70%) had severe depression. But among control 11 (7.87%) had mild depression, 7 (5%) had moderate depression and 2 (1.43%) had severe depression. Depression was more in patients aged 40-60 years (45,42.1%) than in those aged 18-39 years (6,18.2%) which was statistically significant (t = - 3.947, p < 0.001). Both mild, moderate and severe depression were more common among singles, obese, Type 2 DM & patients who were taking both insulin & OHA. Statistically significant depression were observed in poorly controlled DM (HbA1c>8%) compared to fair control (HbA1c 7-8%) (p <0.001, 95% CI = 2.29 to 3.82) and good control (HbA1c < 7%) (p <0.001, 95% CI = 4.25 to 5.98).The likelihood of depression was not significantly associated with different occupation, level of education, residence and duration of DM. Significant positive correlation was observed between DSM-V score and age (r = 0.295, p<0.001),BMI (r = 0.473, p<0.001), duration of DM and HbA1c (r = 0.734, p<0.001) in patients with DM. Conclusion: Our findings demonstrate that there is a higher proportion of depression in patients with DM, which is almost thrice than healthy control. Since patients with DM are at higher risk of developing depression, assessment of depression should be part of the initial and ongoing evaluation of these patients to improve their quality of life. TAJ 2021; 34: No-1: 47-54